2017
DOI: 10.5267/j.msl.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

ICT and accounting system of SMEs in Nigeria

Abstract: This study examined the relationship between ICT and Accounting system of SMEs in Nigeria. The study adopted the survey research design, which involves the collection of data from the Accounting department of SMEs in Nigeria. Primary data was employed and copies of questionnaire were administered to respondents for the purpose of this study. Two hypotheses were formulated and tested using Pearson Product-Moment Correlation Coefficient at a significant level of 1%. Findings revealed a significant relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…Nigeria, as a world's fast-emerging economy and the largest economy in Africa ( Giles, 2018 ; PwC, 2019 ). Nigeria is a choice location for many Asian and European businesses and a fast-growing country for technology utilisation ( Adi, 2015 ; PwC, 2016 ; Ogundana et al., 2016 ; Nigerian Communications Commission, 2018 ). Therefore, this study focused on investigating the link between knowledge transfer and innovation performance of Small and Medium Enterprises in an Informal Economy, such as Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Nigeria, as a world's fast-emerging economy and the largest economy in Africa ( Giles, 2018 ; PwC, 2019 ). Nigeria is a choice location for many Asian and European businesses and a fast-growing country for technology utilisation ( Adi, 2015 ; PwC, 2016 ; Ogundana et al., 2016 ; Nigerian Communications Commission, 2018 ). Therefore, this study focused on investigating the link between knowledge transfer and innovation performance of Small and Medium Enterprises in an Informal Economy, such as Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Technology-based SMEs are globally recognized to be significant to enhancing global economies, especially through their contribution to GDP, advancement of economic competitiveness and tax revenue generation [1] , [2] , [4] , [3] , [9] . However, in Nigeria, there is still dearth in literature, especially with data evidence about the financing strategies that are most significant to facilitating the activities of technology-based SMEs and the role of entrepreneurial competencies on their business growth [8] , [10] . This research benefitted from the ideas of existing research studies.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Several previous studies in this topic were done by Sam et al (2012), Relhan (2013), Tijani and Mohammed (2013), Suyono et al (2016b), Ogundana et al (2017), Ezeagba (2017), Uddin et al (2017), etc. Suyono et al (2016b implemented a computer-based accounting information system for managing the microfinance institutions such as Baitul Maal wa Tamwil (BMT) in Banyumas Region, Indonesia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2011) conducted a study in Spain regarding the effect of AIS application on performance and the results found that there was no significant relationship between the productivity of SMEs and CBAS use. Ogundana et al (2017) examined the relationship between information and communication technology (ICT) and accounting systems in SMEs in Nigeria and the results found a significant relationship between ICT knowledge and the accounting system. Moreover, there is also a significant relationship between ICT adoption through various accounting software packages and the accounting system.…”
Section: Literature Reviewmentioning
confidence: 99%